The Students’ Perception on the Characteristics of Effective and Ineffective English Language Teachers - Khaerati Khaerati (Universitas Negeri Makassar, 2016)
Effective and ineffective English teacher will determine the success of teaching and learning process. This research was conducted to find out the students’ perception on the characteristics of effective and ineffective English language teachers. The methodology employed in this research was qualitative method by applying coding of qualitative data. The main instrument of this research was data in the form of essay. The essays were collected from the students. The data analysis was carried out by following the grounded theory procedure and technique comprised three steps: open coding (inductive), axial coding and selective coding. This research found out that there are several characteristics of effective and ineffective English teacher. They are teacher’s personality, teacher’s appearance, teacher’s classroom performance, material mastery and classroom management. Keywords: effective, ieneffective, perception